THE EVALUATION OF THE ENTERPRISES COMPETITIVENESS IN THE PERIOD OF ECONOMIC INSTABILITY - Vasylenko, V. A. (Science and Transport Progress, 2009)
Approaches to the estimation of competitiveness of an air transport company, which can be used for the improvement of economic position of the company in the conditions of financial crisis, are determined.